Identification of six new Alternaria sulfoconjugated metabolites by high‐resolution neutral loss filtering. (25th August 2015) - Kelman, Megan J.; Renaud, Justin B.; Seifert, Keith A.; Mack, Jonathan; Sivagnanam, Kumaran; Yeung, Ken K.‐C.; Sumarah, Mark W.
<x xml:space="preserve">Abstract</x> Rationale Many species of Alternaria damage important agricultural crops, including small grains and tomatoes. These fungi can produce a variety of secondary metabolites, some of which are toxic to humans and animals. Interest in screening for conjugated or 'modified' mycotoxins has increased because of their tendency to evade traditional analytical screening methods. Two sulfoconjugated Alternaria toxins have been reported and the potential exists for many more. Methods One hundred and forty‐eight Canadian strains of Alternaria spp., about half of them isolated from grain, were grown on Potato Dextrose Agar in Petri dishes for 7 days. Plugs of each strain were removed, extracted and screened by a rapid liquid chromatography (LC)/data‐dependent tandem mass spectrometry (MS2) method in negative electrospray ionization mode. Data generated on an Orbitrap Q‐Exactive mass spectrometer was processed by post‐acquisition neutral loss filtering (NLF). Seven isolates that produced sulfoconjugates of known Alternaria toxins were selected for growth on three additional types of fermentation media. Results Collision‐induced dissociation of sulfoconjugated ions displayed a distinctive neutral loss of SO3 (79.957 Da) that was detected in the MS2 datasets using post‐acquisition NLF. A total of 108 of the 148 isolates screened produced sulfoconjugated metabolites on agar plates. Analysis of the seven isolates grown in liquid culture, on rice and Cheerios, led to the discovery of six new, two previously reported and 30 unidentified sulfoconjugated compounds. Conclusions NLF of HRMS2 data from an Orbitrap Q‐Exactive is a powerful tool for the rapid discovery of sulfoconjugated fungal metabolites. This technique could also be applied to the detection of other important conjugated mycotoxins such as glucosides. The majority of the Canadian isolates of Alternaria spp. studied produced sulfoconjugated metabolites, some of which had no known 'free' Alternaria precursor metabolite, indicating that they are possibly new metabolites. The advantage of sulfoconjugation to Alternaria spp. is unknown, and warrants further study into the mechanisms behind the sulfur assimilatory pathways. Copyright © 2015 John Wiley & Sons, Ltd.